Supported Employment for the Reintegration of Disability Pensioners with Mental Illnesses: A Randomized Controlled Trial - Viering, Sandra; Jäger, Matthias; Bärtsch, Bettina; Nordt, Carlos; Rössler, Wulf; Warnke, Ingeborg; Kawohl, Wolfram (Frontiers in Public Health, 2015)
Work is beneficial for the recovery from mental ilness. Although the approach of individual placement and support (IPS) has been shown to be effective in Europe, it has not yet been widely implemented in European health care systems. The aim of this randomized controlled trial was to assess the effectiveness of IPS for disability pensioners with mental illnesses new on disability benefits in Switzerland. In the study at hand, 250 participants were randomly assigned to either the control or the intervention group. The participants in the intervention group received job coaching according to IPS during two years. The control group received no structured support. Both groups were interviewed at baseline and followed up every six months (baseline, 6, 12, 16, 18, 24 months) for two years. Primary outcome was to obtain a job in the competitive employment. IPS was more effective for the reintegration into the competitive employment market for disability pensioners than the control condition. 32% of the participants of the intervention group and 12% of the control group obtained new jobs in the competitive employment. IPS is also effective for the reintegration into competitive employment of people with mental illness receiving disability pensions.